Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Yan, Xiaobo; Pan, Simiao; Li, Zhihao; Dong, Xiaohui; Tan, Beiping; Long, Shuisheng; Li, Tao; Suo, Xiangxiang; Yang, Yuanzhi (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with L. pentosus at 1.0×107, 1.0×108, 1.0×109 CFU/g, respectively. Five kinds of diets were fed to hybrid grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results showed that (1) consumption of OFO diet significantly increased muscle crude lipid, total cholesterol, and total monounsaturated fatty acids contents and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper (p < 0.05), whereas the addition of L. pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels, increased muscle crude protein content, and enhanced muscle hardness, gumminess, and chewiness compared with FFO or OFO group (p < 0.05). (2) In addition, ingestion of OFO diet significantly increased muscle phenylalanine content and significantly decreased aspartic acid content (p < 0.05), while the addition of L. pentosus restored aspartic acid to the level not significantly different from that of FFO group (p > 0.05). The addition of L. pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine, and alanine content compared to FFO group at the same time (p < 0.05). (3) Furthermore, the intake of OFO diet would lead to deterioration in muscle flavor quality and increase in noxious odors in grouper, and the addition of L. pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly downregulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system (p < 0.05), which was protected against by the potent antioxidant properties of L. pentosus. We recommend the supplementation level of L. pentosus to be 1.0×109 CFU/g under the highly oxidized conditions of the present trial fish oil.